Unsteady aerodynamic performance of a maglev train: the effect of the ground condition. Issue 4 (9th November 2022) - Meng, Shi; Chen, Guang; Zhou, Dan; Meng, Shuang
Abstract: The effect of ground condition on unsteady aerodynamic performance of a maglev train was numerically investigated with an IDDES (Improved Delayed Detached Eddy Simulation) method. The accuracy of the numerical method has been validated by wind tunnel experiments. The flow structure, slipstream and aerodynamic force around the train under stationary and moving ground conditions were compared. Track and ground play a leading role in the influence of wake vortex structure; the flow structure around the train is more complex under the stationary ground boundary condition. Near the nose point of the head and tail vehicles, the peak value of the slipstream under the condition of moving ground is slightly higher than that under stationary ground. In the wake area, the effect of the main vortex structure on both sides of the tail vehicle and the track makes the vortex structure in the wake area stronger than that under moving ground, the slipstream peak is larger and the locus thereof is further forward. In the horizontal direction, the vortex desorption energy near the nose tip of the train is higher on stationary ground, while the vortex desorption energy far from the nose tip of the train is higher on moving ground. Compared with the static ground boundary condition, the resistance coefficient of the head and tail of a maglev train increases by 3.45% and 3.31% respectively under the moving ground boundary condition. The lift coefficient decreases by 157.78% and 5.13%, respectively.